Respons Guru Dalam Menumbuhkan Nilai Mandiri Melalui Pembelajaran IPS Selama Masa Adaptasi Kebiasaan Baru Covid-19 di Jawa Timur - Ahmad Tanfidzi Dharma Putra; Harmanto Harmanto; Aminuddin Kasdi (IAIN Madura, 2020)
The implementation of character education in Indonesia is deemed not optimal, because it has not fully implemented character values to its full potential. The Indonesian government through Presidential Regulation Number 87 in 2017 launched the Strengthening Character Education program in all education units covering nationalist, independent, religious, integrity, and mutual cooperation. The purpose of this study was to document the teacher's response in independent values as one of the values in strengthening character education through social studies learning during the adaption of Covid-19 period. Participants included 19 randomized social studies teachers in East Java. This research is a descriptive study with an instrument form list of interviews. Data in the form of teacher responses were analyzed descriptively. The results showed that 84.2% of teachers had facilitated the growth of independent values in students who were written in the Long Distance Learning Implementation and 52.6% of teachers said that distance learning social studies was less effective, so there needed to be an interesting method for distance learning social studies so the learning become more effective.